2016
DOI: 10.1039/c6dt01457g
|View full text |Cite
|
Sign up to set email alerts
|

hsDNA groove binding, photocatalytic activity, and in vitro breast and colon cancer cell reducing function of greener SeNPs

Abstract: Selenium nanoparticles (SeNPs) have attracted great attention because of their superior optical properties and wide utilization in biological and biomedical studies. This paper reports an environmentally benign procedure of greener monodispersible SeNP synthesis using the reducing power of Trigonella foenum-graecum extract, characterization and their protective effect against unfolded (Herring sperm DNA) hsDNA. We investigated the anti-cancer activity of SeNPs against MCF-7, MDA MB 435 and COLO-205 cells. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…To overcome this unavoidable impact, chemoradiotherapy can be utilized with a radioactive seed to deliver enhanced, efficient and precise radiation. Based on this concept, Bhattacharjee et al 205 investigated a combined in-vivo and in-vitro experiment by utilizing folic acid capped SeNPs (FA-SeNPs) in conjugation with radioactive 125 I seeds to impart enhanced anticancer viability. In comparison with individual treatment, the blend of (FA-SeNPs) and 125 I seeds demonstrated better in-vivo antitumor and lower cytotoxicity in MCF-7 infected mice.…”
Section: Other Biological Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this unavoidable impact, chemoradiotherapy can be utilized with a radioactive seed to deliver enhanced, efficient and precise radiation. Based on this concept, Bhattacharjee et al 205 investigated a combined in-vivo and in-vitro experiment by utilizing folic acid capped SeNPs (FA-SeNPs) in conjugation with radioactive 125 I seeds to impart enhanced anticancer viability. In comparison with individual treatment, the blend of (FA-SeNPs) and 125 I seeds demonstrated better in-vivo antitumor and lower cytotoxicity in MCF-7 infected mice.…”
Section: Other Biological Applicationsmentioning
confidence: 99%
“…Based on this concept, Bhattacharjee et al 205 investigated a combined in-vivo and in-vitro experiment by utilizing folic acid capped SeNPs (FA-SeNPs) in conjugation with radioactive 125 I seeds to impart enhanced anticancer viability. In comparison with individual treatment, the blend of (FA-SeNPs) and 125 I seeds demonstrated better in-vivo antitumor and lower cytotoxicity in MCF-7 infected mice. Yu et al 209 reported that Se nanoparticles in combination with radiation reduces the damage to nearby tissues and enhances the carcinogenic cell affectability to harmful impacts of illumination on breast cancer cell MCF-7 by in-vitro study.…”
Section: Other Biological Applicationsmentioning
confidence: 99%
“…Binding mechanism gives (S3) binding constant (K) between BSA and PdNNs was found in the range of 10 4 M − 1 and number of binding sites (n) between BSA and PdNNs was approximately equal to 1 delineated in Table S3. Which suggested that PdNNs can easily be complex in protein as well as released in desired target areas and shows moderate a nity [52,53].…”
Section: Resultsmentioning
confidence: 99%
“…Interaction between a-AA and DNA was determined by UV-Vis absorption, uorescence measurements, CD measurements, viscosity experiments; thermal denaturation and minor groove displacement assays were demonstrated by a previously reported method. 27 Glide version 5.7 -Schrödinger suite 2013-1 was used for the molecular docking of a-AA-DNA binding. The B-DNA dodecamer d(CGCGAATTCGCG) 2 (PDB ID: 1BNA) structure was copied from the protein data bank (http://www.rcsb.org./pdb).…”
Section: Methodsmentioning
confidence: 99%